The Guidelines of Monastery Management for Spiritual Tourism : A Case Study of Wat Pa Tam Wua Forest Monastery: The Guidelines of Monastery Management for Spiritual Tourism : A Case Study of Wat Pa Tam Wua Forest Monastery - Chaipatanapruck, Keatisak; Kotsupho, Phisit; Vichai, Virot; Ratchawat, Sayam (Journal of Graduate MCU KhonKaen Campus, 2022)
The objects of this research were: 1) to study the concepts and theories of monastery management for spiritual tourism in Buddhism, 2) to study and analyze the practical principles of monastery management for spiritual tourism of Wat Pa Tam Wua forest monastery, Mae Hong Son, 3) to propose guidelines of monastery management for spiritual tourism in Thailand. This research was conducted by the qualitative research method. The researcher has studied primary and secondary and conducted the fieldwork to collect the data by in-depth interviews and participant observations. Then the obtained data were analyzed and the findings were presented by the descriptive approach. The research results were as follow: “Meditation at Monastery” in Thailand followed Buddhist principle “Trisikkha” is an attraction for spiritual tourism. By applying “the seven principles of Sappaya” in monastery managementto support meditators. Also,“Loving Kindness” that has been given to everyone, no racial discrimination. The tourists who came for spiritual practice, will have this impressive experience and learn about loving kindness. “Sangaha-Vatthu 4”principle applying in the monastery management to develop an effective management with warm and friendly environment. The guidelines for operation are divided; 1) The operation in monasteries: the place, the people, the organizing of activities within the monastery, the plan of monastery for spiritual tourism 2) The coordination with agencies outside the monastery : the public relations of the monastery, the tourism development coordination, to create the community’s involvement in monastery management for spiritual tourism.